In the veins of the drowning - Cassidy, Kalie (Cassidy, Kalie. Siren Mage, 2025)
"The monster is always slain ... Imogen Nel is in hiding. Hiding from a cruel kingdom that believes Sirens are monstrous, blood-hungry creatures. Hiding from a king and his captain who viciously hunt her kind. Hiding from her own alluring abilities. By keeping herself from the sea, Imogen's bloodlust is dulled, and her black wings remain concealed beneath her skin. When a neighboring king comes to visit, Imogen can no longer hide. He knows precisely what she is, and he believes she can save their kingdoms from an even greater monster. But Imogen's power threatens to violently reveal itself, and the two form a blood bond that protects them both. They flee together, traversing waters teeming with the undead. As the lines between duty to their people and desire for each other begin to blur, Imogen worries her ancestral powers may not be enough to kill what hunts her--the only way to defeat a monster may be to become one herself"--